A DFT Study on the Mechanism of the Cycloaddition Reaction of CO2 to Epoxides Catalyzed by Zn(Salphen) Complexes. Issue 20 (19th March 2013) - Castro‐Gómez, Fernando; Salassa, Giovanni; Kleij, Arjan W.; Bo, Carles
Abstract The reaction mechanism for the Zn(salphen)/NBu4X (X=Br, I) mediated cycloaddition of CO2 to a series of epoxides, affording five‐membered cyclic carbonate products has been investigated in detail by using DFT methods. The ring‐opening step of the process was examined and the preference for opening at the methylene (Cβ) or methine carbon (Cα) was established. Furthermore, calculations were performed to clarify the reasons for the lethargic behavior of internal epoxides in the presence of the binary catalyst. Also, the CO2 insertion and the ring‐closing steps have been explored for six differently substituted epoxides and proved to be significantly more challenging compared with the ring‐opening step. The computational findings should allow the design and application of more efficient catalysts for organic carbonate formation.